Associations between patient, treatment, or wound‐level factors and venous leg ulcer healing: Wound characteristics are the key factors in determining healing outcomes. Issue 2 (19th November 2019) - Weller, Carolina D.; Bouguettaya, Ayoub; Team, Victoria; Flegg, Jennifer; Kasza, Jessica; Jayathilake, Chathranee
Abstract: Chronic venous leg ulcers are challenging to heal and often recur. This has a significant impact on older individual health and is a financial burden on health care resources. This study aimed to identify factors associated with the healing of venous leg ulcers via secondary examination of data from a previously published prospective randomized controlled trial of elastic and inelastic compression systems. The data from the 45 patients who finished the trial was reanalyzed for a hypothesis generating study. Larger ulcers, higher exudate levels, larger calf circumferences, and longer ulcer duration at baseline were associated with lack of healing at 12 weeks. There was some evidence that NSAID use was associated with an increased likelihood of nonhealing (unadjusted OR for healing, 0.13, 95% CI (0.02, 0.70)). There was no evidence that other variables, including gender and BMI, were associated with healing. The key risk factors for wound healing are largely wound based or inherent to wound development, as these were found to be the factors with the strongest associations in the analysis. Future research should address how and why these factors are associated with wound healing over a longer time frame and explore how NSAIDs may affect wound healing outcomes.